PERAN BALAI LATIHAN KERJA (BLK) KABUPATEN MAGELANG DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA (SDM) - PRAMUSISKA GUMILAR; Achmad Taufiq; Turtiantoro . (Journal of Politic and Government Studies, 2016)
ABSTRACTTraining is an acitivity that aims to improve a person’s skills and and also aims to increase the human resources so that they can compete in the world of work.Vocational training centers in Magelang district is one of the government agencies that provide training and aims to improve the quality of human resources as described earlier.Participants who have attended the training are expected to work according to the skills that have been given. The data were taken from in-depth interview, photos, documents, and observations.According to the results showed that the implementation of the training has been going well as it should.But the overall implementation of the training activities encountered some resistance training are the obstacles related to the condition of facilities and insfrastructure are lacking to meet the needs of training departments and also contstraints regarding the number of instructors that do not coresspond to the number of existing training department.Related cooperation is carried over to the training cooperation is not cooperation employment.The advice given author is a training facility that is more in added and customized with modern equipment.In addtion, it is alsonecessary for cooperation student placement training.With the implementation of these recommendations the training will run well.Keywords : training, human resources, labor